MANAJEMEN AIRWAY PADA PEMBEDAHAN ORIF DENGAN GENERAL ANESTESI LARINGEAL MASK AIRWAY (LMA) - Berliana Marschanda Kholyly; Dimas Fadlyan; Kristina Tasya Aurora Rumagit; Kunti Melati; Randi Piariani; Halima Aulia Ita Maghfiroh (STKIP Subang, 2025)
General anesthesia causes reversible loss of consciousness and pain and requires the use of breathing aids such as a face mask or Laryngeal Mask Airway (LMA) to ensure adequate ventilation during surgery. In surgical procedures such as Open Reduction and Internal Fixation (ORIF), especially on the upper extremities, understanding the mechanisms of general anesthesia, the selection of airway devices, and postoperative risks is important for optimizing perioperative management and patient safety. The objective is to determine the airway status of upper extremity ORIF patients undergoing ORIF surgery with General Anesthesia using LMA. This study is a descriptive observational study with a sample size of 5 patients diagnosed with upper extremity fractures who underwent ORIF surgery at Diponegoro Dua Satu General Hospital in Klaten. All patients had good preoperative airway evaluation results and were categorized as ASA I–III. During the anesthesia procedure, LMA placement was successfully performed in all patients without complications, with adequate and stable spontaneous ventilation throughout the surgery. Intraoperative monitoring showed that the patients' hemodynamic and respiratory parameters, such as SpO₂, ETCO₂, airway pressure, and tidal volume, remained within normal limits without any signs of obstruction or airway complications. Airway management with LMA intubation and invasive monitoring proved to be safe and effective during the ORIF surgical procedure.